Print to fit : the New York Times, Zionism and Israel, 1896-2016 - Auerbach, Jerold S. (Academic Studies Press, 2019)
Ever since Adolph Ochs purchased The New York Times in 1896, its enduring masthead motto - ""All The News That's Fit To Print""--Has become news that fits Times' discomfort with the idea, and since 1948 the reality, of a thriving democratic Jewish state in the historic homeland of the Jewish people.
Series taken from publisher's Web site.
Keywords: New York times.; New York times; Arab-Israeli conflict -- Press coverage -- United States.; Journalism -- Objectivity -- Uniteted States.; Palestine question (1948-); Conflit israélo-arabe -- Couverture de presse -- États-Unis.; LANGUAGE ARTS & DISCIPLINES -- Journalism.; SOCIAL SCIENCE / Media Studies; Arab-Israeli conflict -- Press coverage; Journalism -- Objectivity; United States; Adolph Ochs.; American Jews.; American Journalism.; History of Israel.; Israel.; Middle East policy.; NYT:The New York Times.; New York Times.; Opinion.; State of Israel.; Times.; Zionism.; Zionist.; anti Zionist.; anti semistism in the media.; anti semitisim.; anti-Zionist.; anti-semitism in the media.; anti-semitism.; antisemitism in the media.; antisemitism.; discrimination.; intolerance.; journalism.; journalist.; media.; national identity.; news and media.; news.; newspaper history.; newspapers.; publications.; religious intolerance.